PENGEMBANGAN BOOKLET JARINGAN HEWAN SEBAGAI SUPLEMEN BAHAN AJAR KELAS Xl SMA - Sahara Zetira Rambe (Jurnal Bionatural, 2024)
This review expects to decide the improvement of booklet-put together learning media with respect to creature tissue for class XI understudies of SMA Nurul Islam Indonesia, the level booklet learning media on creature tissue for class XI understudies of Nurul Islam Indonesia. This study utilizes a 4-D improvement model (Innovative work). This examination was completed on The consequences of the review were to deliver a creature tissue booklet learning media item that was created containing creature tissue material. To test the attainability of booklet-based intelligent learning media by approving the items made to the material master group, the typical score was 87% by media specialists, 84% by material specialists, and by Science instructors (field practitioners)90 %. So it tends to be reasoned that the booklet-based intuitive learning media is entirely attainable to use in the science educational experience on creature tissue material.